2006
DOI: 10.1002/hep.21071
|View full text |Cite
|
Sign up to set email alerts
|

Changes in liver and plasma acetylcholinesterase in rats with cirrhosis induced by bile duct ligation

Abstract: Classical studies of cholinesterase activity during liver dysfunction have focused on butyrylcholinesterase (BuChE), whereas acetylcholinesterase (AChE) has not received much attention. In the current study, liver and plasma AChE levels were investigated in rats with cirrhosis induced after 3 weeks of bile duct ligation (BDL). BDL rats showed a pronounced decrease in liver AChE levels (ϳ50%) compared with sham-operated (non-ligated, NL) controls; whereas liver BuChE appeared unaffected. A selective loss of tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 48 publications
3
38
1
1
Order By: Relevance
“…Using nondenaturing polyacrylamide gels stained for AChE activity, the molecular masses of AChE subunits are in the range of 70 to 75 kDa. Analysis by SDS-PAGE and Western blotting by us and others, under fully reducing conditions and with several alternative anti-AChE antibodies, detected bands ranging from 75 to 60 kDa, as well as other species of 55 and 50 kDa, that may have originated by posttranslation modification (12,20,21,74). In a previous study, we confirmed the specificity of the major AChE bands, including the 55-kDa subunit, by AChE immunoprecipitation and probing blots with three alternative anti-human AChE antibodies (21).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Using nondenaturing polyacrylamide gels stained for AChE activity, the molecular masses of AChE subunits are in the range of 70 to 75 kDa. Analysis by SDS-PAGE and Western blotting by us and others, under fully reducing conditions and with several alternative anti-AChE antibodies, detected bands ranging from 75 to 60 kDa, as well as other species of 55 and 50 kDa, that may have originated by posttranslation modification (12,20,21,74). In a previous study, we confirmed the specificity of the major AChE bands, including the 55-kDa subunit, by AChE immunoprecipitation and probing blots with three alternative anti-human AChE antibodies (21).…”
Section: Discussionmentioning
confidence: 77%
“…This would correspond to the 55-kDa subunit that is contained within both AChE tetramers and monomers species (20,21); thus, it cannot be assigned to a particular AChE form. Accordingly, PS1 may coprecipitate either the G 4 or the G 1 ϩG 2 species or both of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that bile duct ligation after 3–4 weeks cause cirrhosis. [5242526] Mild cognitive impairment reported in patients with the liver cirrhosis. [27] Furthermore, in some patients with liver disease and signs of hyperamonia it has been showed that impaired attention, memory, cognitive function, and motor function.…”
Section: Discussionmentioning
confidence: 99%
“…[12] It has been shown that structural and functional impairment of the hepatobiliary systems[3] that cause a failure in bile secretion in hepatocytes or ductular cells or an impairment of bile flow and accumulation of bile salts in the body. [456]…”
Section: Introductionmentioning
confidence: 99%